A atuação do intérprete de Libras: um estudo situacional sobre microexpressões faciais - Cerantola, Giovana Teixeira de Mendonça (Universidade Federal de São Carlos, 2019)
The present work aims to discuss and problematize the concept of impartiality of the interpreter of libras (Brazilian sign Language), from the analysis of the facial microexpressions produced by him, describing the facial expressions displayed by This professional in a situation of interpreting an emotionally charged discourse. Given that the microexpressions are subtle emotions that appear on the face as we try to oppress a specific emotion, the work aims to analyze a video at the time of the interpreter's performance, in a situation in which he has no prior knowledge of the material he will Interpret. Based on these data, we tried to describe the facial microexpressions, in order to evidence possible emotions contained by the interpreter. From the analyses, it was possible to verify by the results of actions taken as impartial, there is an intense work of the professional interpreter to contain formulations that transparethe aspects of his subjectivity. The analysis of microexpressions, however, reveals that in the smallest details of facial gestures, it is possible to identify indices of emotions caused by the stress situation in question. This discussion draws attention to the need to conceive the professional interpreter of pounds as a human being (and not as mere conduit of information from a source A to a destination B), who, acting in situations which put in a situation of discomfort, sometimes , it will manifest, although minimal expressions, complex conceptions and perceptions of its subjectivity.
The performance of the Libras interpreter: a situational study on facial microexpressions
Keywords: Intérprete de Libras; Imparcialidade; Emoções; Microexpressões faciais; LINGUISTICA, LETRAS E ARTES::LINGUISTICA